2008
DOI: 10.1002/jbm.a.32121
|View full text |Cite
|
Sign up to set email alerts
|

Biological response to micron‐ and nanometer‐sized particles known as potential wear products from artificial hip joints: Part II: Reaction of murine macrophages to corundum particles of different size distributions

Abstract: Macrophages play a pivotal role in tissue reaction and immune response. They recognize, phagocytose particles and generate cytokines to influence local cellular reactions. Friction and wear of implant components usually generates microparticles (MP) in a size range of 1-10 mum and nanoparticles (NP) in the range of 10-1000 nm. To investigate the possible impact of MP or NP on cellular reactions, we exposed murine macrophages (RAW264.7) to corundum MP and NP. The same mass was used in both NP and MP cell cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…This cell line has been used by previous investigators performing similar assays [30][31][32] and has the advantages of being a robust, stable, established cell line with predictable uniform cytokine responses. The RAW264.7 cells were grown, maintained, and assayed in DMEM with 10% heat-inactivated fetal bovine serum.…”
Section: Cells and Cell Culturementioning
confidence: 98%
“…This cell line has been used by previous investigators performing similar assays [30][31][32] and has the advantages of being a robust, stable, established cell line with predictable uniform cytokine responses. The RAW264.7 cells were grown, maintained, and assayed in DMEM with 10% heat-inactivated fetal bovine serum.…”
Section: Cells and Cell Culturementioning
confidence: 98%
“…Larger particles (>7μm) were shown to have no effect on bone resorption and cytokine production. In another study using mouse RAW264.7 macrophages, corundum particles in the nanometer size induced higher pro-inflammatory cytokine production and more giant cell formation than micrometer sized particles 48 . Human THP1 macrophage cells exposed to conventional or highly cross-linked UHMWPE particles induced significant pro-inflammatory cytokine production when the particles were of a larger size (>10μm); cells exposed to conventional UHMWPE particles showed higher cytotoxicity with small particles (0.7μm) 47 .…”
Section: Challengesmentioning
confidence: 95%
“…The biological response of immune cells to wear particles is dependent on the particle composition 43 , dose 44 , 45 , size 44 , 46-48 , shape, and surface chemistry, energy and topography 49 . In one study, periprosthetic tissues from patients with aseptic loosening of implants were transplanted into the muscles of immunodeficient mice.…”
Section: Challengesmentioning
confidence: 99%
“…Attempts by the immune system to consume and remove these wear particles often leads to a state of a chronic inflammation. It has also been observed that wear debris cleared from the joint space by lymph or blood flow collects in the lymph nodes and other organs of the immune system 42, 44, 45…”
Section: Mechanical Failure Of Polymeric Biomaterialsmentioning
confidence: 99%